Diagnosis of giant cell arteritis by temporal artery biopsy is associated with biopsy length - Ruediger, Carlee; Ninan, Jem; Dyer, Kathryn; Lyne, Suellen; Tieu, Joanna; Black, Rachel J.; Dodd, Thomas; Lester, Susan; Hill, Catherine L. (Frontiers in Medicine, 2022)
Aims Temporal artery biopsy (TAB) is a widely used method for establishing a diagnosis of Giant Cell Arteritis (GCA). The optimal TAB length for accurate histological GCA diagnosis has been suggested as 15 mm post-fixation (15–20 mm pre-fixation). The aim of this study was to determine the relationship between a histological GCA diagnosis and optimal TAB length in the South Australian (SA) population. Materials and methods Pre-fixation TAB length (mm) was reported in 825/859 of all samples submitted to SA Pathology between 2014 and 2020 from people aged 50 and over. When more than one biopsy was taken, the longest length was recorded. Analyses of both TAB length and TAB positive proportions were performed by multivariable linear and logistic regression analysis, including covariates sex, age, and calendar year. Results The median age of participants was 72 (IQR 65, 79) years, 549 (66%) were female. The TAB positive proportion was 172/825 (21%) with a median biopsy length of 14 mm (IQR 9, 18). Biopsy length (mm) was shorter in females (p = 0.001), increased with age (p = 0.006), and a small positive linear trend with calendar year was observed (p = 0.015). The TAB positive proportion was related to older age (slope/decade: 6, 95% CI 3.6, 8.3, p < 0.001) and to TAB length (slope/mm 0.6, 95% CI 0.2, 0.9, p = 0.002), but not sex or calendar year. Comparison of models with TAB length cut-points at 5, 10, 15, 20 mm in terms of diagnostic yield, receiver operating characteristics and Akaike Information Criteria confirmed ≥ 15 mm as an appropriate, recommended TAB length. However, only 383 (46%) of the biopsies in our study met this criteria. The diagnostic yield at this cut-point was estimated as 25% which equates to an expected additional 30 histologically diagnosed GCA patients. Conclusion This study confirms that TAB biopsy length is a determinant of a histological diagnosis of temporal arteritis, and confirms that a TAB length ≥ 15 mm is optimal. Approximately half the biopsies in this study were shorter than this optimal length, which has likely led to under-diagnosis of biopsy-proven GCA in SA. Further work is needed to ensure appropriate TAB biopsy length.